IMPLEMENTATION OF TARGET THERAPY IN RELAPSED CLASSIC HODGKIN LYMPHOMA: A SINGLE-CENTER EXPERIENCE (Herald of the National Children's Medical Center, 2025)
Classic Hodgkin lymphoma (cHL) accounts for approximately 5-6% of childhood malignancies and is one of the most curable cancers in children. While the disease can be cured with limited resources, relapsed or refractory (RR) cHL remains a challenge for up to 15% of patients. Fortunately, Brentuximab vedotin (BV) and anti-PD-1 blocking antibodies, such as nivolumab and pembrolizumab, have proven to be highly effective treatments for cHL and have revolutionized disease management.